Game Developers' Approaches to Communicating Climate Change - Foltz, Anouschka; Williams, Claire; Gerson, Sarah A.; Reynolds, David J.; Pogoda, Sarah; Begum, Taslima; Walton, Sean P. (Frontiers in Communication, 2019)
Educational games are potential tools for communicating climate science to the public and thus improving public understanding of climate change. In this article we explore the use of co-design methodologies, a participatory open design process, to communicate climate change to a wider audience. To this end, we hosted Climate Jam 2018, a game jam with the objective of creating games to communicate climate change science and to gain insight into how developers approach educational game design. The inclusive event attracted professional game developers and hobbyists from four continents. Participants received a science pack with scientific information about climate change and completed a pre- and post-game-jam survey containing questions relating to climate change, motivations, and game design principles. We present a description of select games that highlight different approaches to communicating climate change to a general audience. Additional results from the surveys showed that few game developers engaged with the science pack and other resources in depth, that communicating climate science was of medium interest to game developers, and that the games’ potential learning effects relate mostly to memorizing and recalling the information communicated in the games. The results are discussed with respect to improving communication between scientists and game developers in the co-creation process.